Leaf Saponins of Quillaja brasiliensis as Powerful Vaccine Adjuvants - Morais, Víctor (2025)
Vaccine adjuvants are non-immunogenic agents that enhance or modulate immune responses to co-administered antigens and are essential to modern vaccines. Despite their importance, few are approved for human use. The rise of new pathogens and limited efficacy of some existing vaccines underscore the need for more advanced and effective formulations, particularly for vulnerable populations. Aluminum-based adjuvants are commonly used in vaccines and effectively promote humoral immunity. However, they mainly induce a Th2-biased response, making them suboptimal for diseases requiring cell-mediated immunity. In contrast, saponin-based adjuvants from the Quillajaceae family elicit a more balanced Th1/Th2 response and generate antigen-specific cytotoxic T cells (CTL). Due to ecological damage and limited availability caused by overharvesting Quillaja saponaria Molina barks, efforts have intensified to identify alternative plant-derived saponins with enhanced efficacy and lower toxicity. Quillaja brasiliensis (A.St.-Hil. and Tul.) Mart. (syn. Quillaja lancifolia D.Don), a related species native to South America, is considered a promising renewable source of Quillajaceae saponins. In this review, we highlight recent advances in vaccine adjuvant research, with a particular focus on saponins extracted from Q. brasiliensis leaves as a sustainable alternative to Q. saponaria saponins. These saponin fractions are structurally and functionally comparable, exhibiting similar adjuvant activity when they were formulated with different viral antigens. An alternative application involves formulating saponins into nanoparticles known as ISCOMs (immune-stimulating complexes) or ISCOM-matrices. These formulations significantly reduce hemolytic activity while preserving strong immunoadjuvant properties. Therefore, research advances using saponin-based adjuvants (SBA) derived from Q. brasiliensis and their incorporation into new vaccine platforms may represent a viable and sustainable solution for the development of more less reactogenic, safer, and effective vaccines, especially for diseases that require a robust cellular immunity.